The challenge of liver resection in benign solid liver tumors in modern times – in which cases should surgery be done? - Hau, Hans-Michael; Kloss, Anne; Wiltberger, Georg; Jahn, Nora; Krenzien, Felix; Benzing, Christian; Schmelzle, Moritz; Seehofer, Daniel; Atanasov, Georgi; Bartels, Michael (Zeitschrift für Gastroenterologie, 2017)
Background Due to improved diagnostical and therapeutical approaches, benign liver tumors represent a challenge in clinical management. We here report our experience with patients undergoing liver resection for benign liver tumors.Methods 188 One hundred eighty-eight consecutive patients, who underwent surgery for solid benign liver tumors from 1992 – 2014, were analyzed retrospectively. The focus was on diagnostic pathways, indications for surgery, and perioperative and postoperative quality of life (QoL).Results Of 188 patients, 100 had focal nodular hyperplasia (FNH) (53.2 %), 33 had hepatocellular adenoma (17.5 %), and 55 had hemangioma (29.3 %). In most patients, there was more than one 1 indication for liver resection, including tumor-associated symptoms (n = 82, 43.6 %), suspicion of malignancy (n = 104, 55.3 %), tumor disease in the medical history (n = 48, 25.5 %), or tumor enlargement (n = 27, 14.4 %). Serious complications (>grade III;, Clavien-Dindo) occurred in 9.5 % of patients. Perioperative mortality was 0.5 %. Patient pain scores decreased over time (p < 0.001). QoL after liver resection significantly improved (p = 0.007).Conclusion Uncertainty of the tumor entity remains an issue in preoperative diagnostics. If indicated, liver resection for benign liver tumors represents a safe approach and leads to significant improvements of QoL.
Keywords: Benigne Lebertumore; Leberresektion; Diagnostische Algorithmen; Lebensqualität